El punto de vista panorámico en la literatura europea decimonónica - Cuvardic García, Dorde (2006)
Rooted in the satire of the Grecolatin Antiguity, the panoramic pint of view is a typical convention of the literary, artistic and scientific discourses of the first half of IXI century Europe. This approach has different functions: it provokes either a critical distance facing the observed reality or a proud identification with society. This article then analyses the use of literature of manners and realism in Spanish literature taking into account authors such as Mariano José de Larra and Mesonero Romanos and the first chapter of Leopoldo Alas “Clarín” La Regenta.